Association between 5HT2A polymorphism and selective serotonin re‐uptake inhibitor (SSRI)‐induced sexual desire disorder (SDD) among Malaysian women. (17th April 2013) - Masiran, Ruziana; Sidi, Hatta; Mohamed, Zahurin; Mohamed Saini, Suriati; Nik Jaafar, Nik Ruzyanei
Abstract: Introduction: SSRIs are known for their sexual side‐effects with a variable rate of sexual dysfunction (SD). 5HT2A (rs6311) single nucleotide polymorphism (SNP) was found to have significant association with SD. The purpose of this study was to determine the prevalence of female SDD, its clinical correlates and association with 5HT2A (rs6311) SNP in patients with major depressive disorder (MDD) treated with SSRIs. Methods: This was a cross‐sectional study. We evaluated 95 female outpatients with MDD treated with SSRIs who were in remission. Outcome measures were stratified by the presence or absence of SDD. A buccal swab was obtained from each patient and sent for genotyping in the Pharmacogenomics and Medical Biotechnology Laboratory of Universiti Malaya. Results: The overall prevalence of female SD was 32.6%. The prevalence of female SDD was 62.1%. Those with arousal problem, lubrication problem, sexual satisfaction problem, orgasm problem and problematic marriage were more likely to have sexual desire disorder. The majority of participants who had sexual desire disorder had genotype TT (42.4%) but there was no significant association observed. After controlling for age, number of children, education level, SSRI type, lubrication problem, orgasm problem, satisfaction problem and marital problem, only arousal problem significantly enhanced the presence of sexual desire disorder by 8.5 times (odds ratio = 8.46, 95% confidence interval = 1.24–57.58; P = 0.018). Discussion: This study showed that there was no significant association between SDD and the 5HT2A (rs6311) SNP. Arousal problem significantly enhanced the presence of sexual desire disorder.